Challenges Of Piano Performance In The 21st Century - Shahzod Nuridinov (Genius Publishing Group, 2025)
This article examines the pressing issues emerging in the field of piano performance in the 21st century. The focus is placed on increasing technical complexity, challenges of interpretation, the influence of digital technologies, and the shifting expectations of modern audiences. The study aims to analyze current trends in the development of contemporary piano performance practice.
Keywords: piano performance; modern musical technique; interpretation